Perceived Safety Climate in Operating Rooms and Its Relationship with the Awareness of the Operating Room Staff about the Surgical Smoke Hazards: A Cross-Sectional Study - Omid Zadi Akhuleh; Abbas Dadashzadeh; Aysan Judi (Tehran University of Medical Sciences, 2022)
Background and Aim: Surgical smoke (SS), is caused by the use of high temperature devices such as electrocautery, laser and ultrasonic scalpel, which are used for cutting and coagulation of tissue during surgery, is considered as a serious threat to the health of operating room (OR) personnel. Various studies have identified the workplace safety climate as one of the main causes of the occurrence or prevention of occupational hazards. This study was conducted with the aim of Perceived Safety Climate (PSC) in ORs and its relationship with the awareness of the OR staff about the SS hazards. Materials and Methods: This cross-sectional study was conducted from April 2021 to July 2022 in the ORs of 26 public hospitals affiliated to Tabriz University of Medical Sciences. In this research, 396 surgical and anesthesia technologists were included in the study by stratified random sampling. Data were collected using a demographic questionnaire, PSC questionnaire and awareness about the hazards of SS questionnaire and analyzed using SPSS software Results: The knowledge of the OR staff regarding the hazards of surgical smoke was evaluated at a moderate level with a mean and standard deviation of 9.82±4.32 (range 0 to 21). The average knowledge score of surgical technologists (11.1±4.56) regarding the hazards of surgical smoke was significantly higher than the average score of anesthesia technologists (8.75±4.1)(P=0.02). The PSC in the OR was evaluated at moderate level with a mean and standard deviation of 62.15±11.1 (range 19 to 95). The results of linear regression analysis showed that the effect of PSC in increasing the awareness of OR staff about the hazards of SS was significant (P=0.001). By increasing one score to the total score of the PSC, the awareness score increases by 0.201. Conclusion: The safety climate of the OR can predict the awareness of the hazards of SS among OR staff. It is recommended to adopt strategies such as educating personnel about the hazards of SS and how to prevent it, creating a suitable supportive environment for personnel, and providing suitable protective facilities to prevent OR staff from being exposed to SS.